Analysis of Cargo Handling Efficiency on Mt. Golden Sky Hana: Procedures and Performance - Supriatna, Arief; Laksmana, Boy; Jayanti, Putri Dwi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research evaluates the cargo handling processes aboard the MT. Golden Sky Hana, focusing on the effectiveness of loading and unloading operations. Using qualitative methods, including direct observations and structured interviews, the study assesses procedural adherence, crew competency, equipment utilization, communication efficiency, and safety practices. The findings reveal that 95% of the cargo handling activities are rated as